Classifying cold‐stress responses of inbred maize seedlings using RGB imaging. (2nd January 2019) - Enders, Tara A.; St. Dennis, Susan; Oakland, Justin; Callen, Steven T.; Gehan, Malia A.; Miller, Nathan D.; Spalding, Edgar P.; Springer, Nathan M.; Hirsch, Cory D.
Abstract: Increasing the tolerance of maize seedlings to low‐temperature episodes could mitigate the effects of increasing climate variability on yield. To aid progress toward this goal, we established a growth chamber‐based system for subjecting seedlings of 40 maize inbred genotypes to a defined, temporary cold stress while collecting digital profile images over a 9‐daytime course. Image analysis performed with PlantCV software quantified shoot height, shoot area, 14 other morphological traits, and necrosis identified by color analysis. Hierarchical clustering of changes in growth rates of morphological traits and quantification of leaf necrosis over two time intervals resulted in three clusters of genotypes, which are characterized by unique responses to cold stress. For any given genotype, the set of traits with similar growth rates is unique. However, the patterns among traits are different between genotypes. Cold sensitivity was not correlated with the latitude where the inbred varieties were released suggesting potential further improvement for this trait. This work will serve as the basis for future experiments investigating the genetic basis of recovery to cold stress in maize seedlings.